Test-retest reliability of the computerized rotational head impulse test in the pediatric population - Mittendorf, Nicole; Reddy, Tarryn Marisca; Heinze, Barbara; Kiderman, Alex; González, Jorge (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: This study aimed to determine the test-retest reliability of the computerized rotational head impulse test (crHIT) as an additional clinical tool to assess horizontal semi-circular canal (HSCC) function in pediatric population. Methods: To determine the test re-test reliability of the crHIT, the study included 29 normally developing children with a mean age of 12.2 years±2.7 (range: 8-17 years) with no history of vestibular symptoms and disorders. Participants underwent two crHITs within one session and one crHIT in the following session. Each crHIT included one protocol using an earth fixed target. The test-retest reliability was determined using a quantitative research approach with a repeated measures design. Results: Mean angular vestibulo-ocular reflex (aVOR) gain of 1.01 (session 1), 1.00 (session 2), and 1.01 (session 3) were obtained. Regression analysis revealed no significant difference for leftward rotations within-session (p=0.608) and between-session (p=0.318) for the differences measured. The same was seen for rightward rotations revealing no significant difference within-session (p=0.631) and between-session (p=0.523). Conclusions: The crHIT is a reliable clinical tool in assessing HSCC functioning in the pediatric population as it demonstrates good test-retest repeatability. The crHIT is a valuable complementary assessment to the video head impulse test (vHIT), since it is well tolerated by children, it is simple to administer and head velocities of >100°/sec are easily attainable. Extending the pediatric vestibular test battery with crHIT can be a valuable diagnostic tool without adding to the overall test time.